The Influence of a Deep Learning Approach Using Augmented Reality on Elementary School Students' Curiosity in the Natural and Social Sciences (IPAS) Subject - Bilqis Billbina; Nur Asyiah; Aliet Noorhayati Sutisno (FKIP - Universitas Riau, 2026)
Curiosity is a fundamental character trait that should be cultivated from the early years of elementary education, particularly in Natural and Social Sciences (IPAS) learning, which requires students to actively observe and explore surrounding phenomena. However, IPAS instruction on the Solar System topic remains largely theoretical and teacher-centered, resulting in limited student engagement and underdeveloped curiosity. This study aimed to examine the implementation, level, and influence of the Deep Learning approach assisted by Augmented Reality (AR) media on students' curiosity in the Solar System topic. A Pre-Experimental method with a One-Group Pre-test-Post-test design was employed, involving 33 sixth-grade students selected through purposive sampling. Data were collected using questionnaires, observation sheets, and student worksheets (LKPD), then analyzed using descriptive statistics and the Wilcoxon Signed Rank Test. Observation results indicated a curiosity engagement rate of 76.56%. The mean curiosity score increased from 65.94 (pre-test) to 71.30 (post-test), with the Wilcoxon test yielding Z = −4.634 and a significance value of < 0.001 (p < 0.05), leading to the rejection of H₀. It is concluded that the Deep Learning approach assisted by Augmented Reality significantly enhances students' curiosity in IPAS learning.